Agricultural automation: A strategic dilemma of a rich Indian farmer. Issue 2 (November 2021) - Srivastava, Shashi Kant
Mr. Jang Bahadur Singh Bagga, a wealthy farmer based in one of the most prosperous states in India, Punjab, was deep in thought pondering over a problem that was occupying his mind. In the face of the havoc caused by COVID-19, Prime Minister Narendra Modi on 24 March 2020 announced a 3-week unprecedented nation-wide lockdown with just 4-hour notice period. Though Bagga realized that the lockdown was a necessary step to arrest the pandemic, nonetheless he was extremely worried because it was nearly time for him to harvest his wheat crop. His worry turned to panic when the lockdown was extended further for another 15 days, and then another 2 weeks, and gradually to over 2 months. While some of the restrictions had been lifted now, the problem was far from solved as most of the migrant labor that worked in the fields had returned to their villages with no signs of them returning to work soon. With crops standing in his fields, waiting to be harvested, Bagga was faced with a dilemma—should he invest in modern machinery for his agricultural activity or stick to manual labor, as was the common practice in the country? The case is suitable to teach MBA students MS Excel, information technology concepts, and business economics. It is also well-suited for executive education. The case is in the form of a story, enabling course participants to engage in experiential learning through decision-making. The learners are also provided details of the actual process of farming in India as also the necessary data to support decision-making.